Rootkit Detection Experiment within a Virtual Environment - Toldinas, J.; Rudzika, D.; Štuikys, V.; Ziberkas, G. (Elektronika ir Elektrotechnika, 2010)
In the context of virtual environments, the security problems are highly important. The paper presents some results of experiments we have carried out within the real virtual machine environment through modeling aiming to identify dependencies between the virus, called Rootkits, detection time and the virtual machine memory size. Rootkits exploit kernel vulnerabilities and gain privileges (popularity) within any system, virtual or not. The basic result of the paper is as follows: 1) the Rootkits detection methodology for the virtual environment when the memory size of a virtual machine is changing; 2) dependences between the virtual machine memory size and Rootkit detection time.